A combined crystallographic and theoretical study of weak intermolecular interactions in crystalline squaric acid esters and amides. Issue 22 (26th May 2017) - Prohens, Rafel; Portell, Anna; Font-Bardia, Mercè; Bauzá, Antonio; Frontera, Antonio
Abstract : We report the synthesis and X-ray solid state structures of five squaric acid derivatives. All compounds form interesting supramolecular assemblies in the solid state that have been analyzed using high level DFT calculations. Abstract : We report the synthesis and X-ray solid state structures of five squaric acid derivatives, i.e. a zwitterionic compound, namely 3-hydroxy-4-(2-pyridin-2-yl-ethylamino)cyclobut-3-ene-1, 2-dione (1 ), a squaramide monoester, 3-ethoxy-4-(2-pyridin-2-yl-ethylamino)cyclobut-3-ene-1, 2-dione (2 ), two differently solvated (EtOH and DMSO/water) disquaramides 3, 4-bis((4-hydroxyphenethyl)amino)cyclobut-3-ene-1, 2-dione (3 and4, respectively), and a mixed hydrogen squarate and disquarate 2-(2-aminoethyl)pyridinium salt (5 ). All compounds form interesting supramolecular assemblies in the solid state that have been analyzed using high level DFT calculations and Bader's theory of "atoms-in-molecules". An intricate combination of ion-pair and H-bonding interactions along with π–π stacking and anion–π contacts of the cyclobutenedione rings is crucial for the formation of the supramolecular assemblies in the solid state.